The Effect of Adverse Childhood Experiences (ACEs) and Positive Reinforcement on the Self-Control of Adolescents in Foster Care Based on the Mediating Role of Cognitive Flexibility - Sabeti Yazdi, Majid; Paydariniyam, Mohammad; Omidi, Azam; Gharibnavaz Esfandabadi, Elham; Gandominejad, Zohreh (International Journal of Education and Cognitive Sciences, 2025)
Purpose: Growing up in foster care can significantly influence the psychosocial development and mental health of adolescents. This study aimed to explore how adverse childhood experiences and positive reinforcement affect the self-control of foster care adolescents through the mediating factor of cognitive flexibility. Methods and Materials: The current study utilized a descriptive-correlational design with a cross-sectional research approach, employing the structural model method and path analysis to investigate the influence of the mediator variable. The statistical population for this research comprised all adolescents in foster care in Tehran from July to October 2023. The study's sample consisted of 129 individuals selected through random sampling. The assessment tools used in the study included the Psychological Flexibility Questionnaire (PFQ), Values in Action - Inventory of Strengths (VIA-IS), Brief Self-Control Scale (BSCS), and the Adverse Childhood Experiences Questionnaire (ACEQ). Data analysis was carried out using SPSS version 27 to describe the data, with the Pearson correlation method utilized, while JASP version 19 was employed to examine the relationships between variables. The study's p-value was established at 0.05. Findings: The findings indicated that the positive reinforcement variable had a significant positive direct impact on self-control (β= 0.068, p